Salesperson Dual Agency in Price Negotiations. (March 2021) - Lawrence, Justin M.; Scheer, Lisa K.; Crecelius, Andrew T.; Lam, Son K.
When should business-to-business firms encourage their salespeople to advocate for the customer in pricing negotiations? This research extends dual agency theory to the sales domain to address this question. In Study 1, the authors examine discount negotiations with secondary data from a major U.S. distributor. They find that the customer and seller both experience the most favorable outcomes when the salesperson advocates strongly for both parties; advocacy for either party alone is counterproductive. Study 2 confirms these results using matched survey, pricing, and profit data and demonstrates a key boundary condition: broad customer–seller ties enable the synergy between customer advocacy and seller advocacy by enhancing the firms' abilities to monitor the salesperson. In Study 3, experiments with business-to-business buyers replicate key findings and provide evidence for theorized mechanisms. This research emphasizes the interdependence between the salesperson's dual roles and demonstrates how the salesperson can serve as an effective agent of both the customer and seller, thereby mitigating challenges associated with role conflict.